Memorandum of Agreement Between the US Air Force and the Alaska State Historic Preservation Office Regarding the Environmental Restoration of Seven Distant Early Warning Sites, Alaska - Moes, Steven J.; Bittner, Judith E. (611th Air Support Group, United States Air Force, 2005)
A Memorandum of Agreement (MOA) between the United States Air Force and the Alaska State Historic Preservation Office regarding the environmental restoration of seven distant early warning sites in Alaska that are also eligible for the National Register of Historic Places. These sites include Point Lay, Wainwright, Point Barrow, Point Lonely, Oliktok, Bullen Point, and Barter Island. The United States Air Force proposes to remove original material from the seven historic properties in the execution of environmental restoration and demolition; and spur road construction at Oliktok. This document also includes Appendix I; a demolition schedule and list of facilities for Section 106 consultation.